Bubble breaths relaxation training for kindergarten teachers - Katrim Alifa Putrikita; Mulianti Widanarti (Universitas Muhammadiyah Magelang, 2023)
One of the problems in early childhood is adjustment to teachers and friends in kindergarten. This problem can cause anxiety in children. In early childhood, the anxiety will cause tantrums because children have difficulty defining their emotions. Therefore, kindergarten teachers need to master the skill to reduce anxiety in children. Based on that, bubble breaths relaxation training is important to kindergarten teachers. Bubble breaths relaxation training is conducted at Bianglala School. The purpose of this training is to provide knowledge and skills about bubble breaths relaxation for kindergarten teachers. The knowledge scale is given for measuring data before and after training. Based on the results of these measurement, there was an increase in knowledge of all participants after the training. Skill improvement can be seen from the practice process, the teachers have succeeded in practicing bubble breaths relaxation, and have been able to provide appropriate bubble breaths relaxation instructions for their students.